2017
DOI: 10.1002/hrm.21886
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high‐performance work systems on transformational leadership and team performance: Investigating the moderating roles of organizational orientations

Abstract: This study integrates strategic human resource management (SHRM) and transformational leadership (TFL) literatures to address gaps in each of the two literatures. Building on the concept of strategically targeted HRM systems and the contingency perspective in SHRM, we propose that an organization's high‐performance work system (HPWS) affects team managers' TFL, and that the emergence of TFL and the effectiveness of TFL on team performance are contingent on organizational adaptation and efficiency orientations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 90 publications
(212 reference statements)
5
49
1
Order By: Relevance
“…Coupled with the preceding interpretation, it is intuitively plausible that as strategically oriented HPWS shapes the context in which leadership is exercised, it may exert its influence on employee reactions through a corresponding strategically focused leadership such as service leadership. Indeed, Han et al () reported an organisational‐level transformational leadership‐oriented HPWS to relate to team performance through transformational leadership. This line of research dovetails with the growing interest in line managers' involvement in the implementation of HPWS (Sikora, Ferris, & Van Iddekinge, ) but must be refocused to examine not only how line managers' enactment of HPWS leads to performance but also promotes human resource sustainability and ultimately, performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coupled with the preceding interpretation, it is intuitively plausible that as strategically oriented HPWS shapes the context in which leadership is exercised, it may exert its influence on employee reactions through a corresponding strategically focused leadership such as service leadership. Indeed, Han et al () reported an organisational‐level transformational leadership‐oriented HPWS to relate to team performance through transformational leadership. This line of research dovetails with the growing interest in line managers' involvement in the implementation of HPWS (Sikora, Ferris, & Van Iddekinge, ) but must be refocused to examine not only how line managers' enactment of HPWS leads to performance but also promotes human resource sustainability and ultimately, performance.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has drawn attention to the interrelationship between HPWS and leadership in promoting performance. For example, Han, Liao, Taylor, and Kim (2017) documented how a strategically oriented HPWS affects team performance through a strategically appropriate leadership style. In a slightly different vein, Weller, Süß, Evanschitzky, and Von Wangenheim (2019) reported HPWS consensus and the well-being indicator of job satisfaction as pathways transmitting the effects of transformational leadership onto customer satisfaction.…”
Section: Moderated Mediationmentioning
confidence: 99%
“…Additionally, our work builds on others that suggest that HR and leaders directly affect each other. For example, Han, Liao, Taylor, and Kim () found a firm's high‐performance work system affects team managers' transformational leadership, and Zhu, Chew, and Spangler () found CEO transformational leadership affected a firm's human‐capital‐enhancing HR management. Our study extends this body of literature by exploring alternative synergies between HR and CEO charisma in small firms.…”
Section: Discussionmentioning
confidence: 99%
“…• leadership may have an indirect effect on outcomes through HRM practices, or HRM practices may have an indirect effect on outcomes through leadership. For example, transformational CEOs are likely to adopt skill-based HRM practices (Lopez-Cabrales, Bornay-Barrachina, and Diaz-Fernandez 2017) and human-capital enhancing HRM practices (Zhu, Chew, and Spangler 2005), which, in turn, will influence organizational outcomes; • organizational-level transformational leadership-enhancing HRM practices may influence team-level transformational leadership, which, in turn, will impact team creativity (Han et al 2018); • leadership may strengthen the influence of HRM practices on outcomes, or HRM practices may strengthen the influence of leadership on outcomes. For example, the CEO's charismatic leadership would strengthen the positive relationship between high-commitment HR practices and organizational performance (McClean and Collins 2019).…”
mentioning
confidence: 99%